Organic Thin‐Film Transistors as Cannabinoid Sensors: Effect of Analytes on Phthalocyanine Film Crystallization (Adv. Funct. Mater. 7/2022). (8th February 2022) - Comeau, Zachary J.; Rice, Nicole A.; Harris, Cory S.; Shuhendler, Adam J.; Lessard, Benoît H.
Abstract : Cannabinoid Sensors In article number 2107138, Adam J. Shuhendler, Benoît H. Lessard, and co‐workers use phthalocyanine (Pc) based organic thin‐film transistors (OTFTs) in combination with a cannabinoid‐sensitive chromophore (Fast Blue BB) to detect Δ 9 ‐tetrahydrocannabinol (THC). Choice of the Pc central atoms and peripheral substitutions provides unique interactions between the Pc, cannabinoid, and chromophore, inducing a significant film recrystallization leading to changes in OTFT performance.